Electrodeposition of tin from EMI⋅BF4⋅Cl room temperature molten salts - Morimitsu M.; Nakahara Y.; Iwaki Y.; Matsunaga M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The electrochemistry of Sn(II) was investigated with cyclic voltammetry and chronoamperometry in the 1-ethyl-3-methylimidazolium tetrafluoroborate molten salt containing free chloride ions (EMI ⋅BF4 ⋅Cl) originated from the mixture of EMIC and NaBF4 (60:40 mol%). The well defined redox waves for the electro deposition and dissolution of tin were observed on a platinum electrode at 303 K. The deposition of tin proceeded through a quasi-reversible step with two electron transfer, and the deposited tin was sufficiently recovered during oxidation. The experimental current-time transient coincided with the theory based on one-dimensional diffusion control.